Solar cell, multi-junction solar cell, solar cell module, and photovoltaic power generation system
The integration of a cuprous oxide p-type light absorbing layer, an n-type layer, and a first metal compound with specific coverage and composition in solar cells addresses the challenge of achieving high conversion efficiency, suppressing defects, and maintaining low costs.
Patent Information
- Application Number
- JP2023152083
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-20
- Publication Date
- 2025-04-02
- Estimated Expiration
- 2043-09-20
AI Technical Summary
Existing solar cells face challenges in achieving high conversion efficiency while maintaining low costs and using abundant materials.
The solar cell design incorporates a p-type light absorbing layer made of cuprous oxide, an n-type layer, and a first metal compound between the p-type light absorbing layer and the n-type layer, with a coverage rate of 10% to less than 100%, using elements like Al, Hf, Zr, or B.
This configuration enhances the conversion efficiency of solar cells by suppressing oxygen extraction from the cuprous oxide layer, reducing defects, and improving open-circuit voltage, while maintaining high transmittance and reducing the thickness of the first metal compound to avoid insulation issues.
Smart Images

Figure 2025044490000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a solar cell, a multi-junction solar cell, a solar cell module, and a photovoltaic power generation system. [Background technology]
[0002] One of the new solar cells is made of cuprous oxide (Cu 2 There are solar cells that use CuO as the light absorption layer. 2 O is a wide-gap semiconductor. Cu 2 O is a safe and inexpensive material made from copper and oxygen, which are abundant on Earth, and is therefore expected to realize highly efficient, low-cost solar cells. [Prior art documents] [Non-patent literature]
[0003] [Non-Patent Document 1] Johannes Lockingera et. al., The use of HfO2 in a point contact concept for front interface passivation of Cu(In,Ga)Se2 solar cells, Solar Energy Materials and Solar Cells 195 (2019) 213-219. Summary of the Invention [Problem to be solved by the invention]
[0004] The problem to be solved by the present invention is to provide a solar cell, a multi-junction solar cell, a solar cell module, and a solar power generation system that are excellent in conversion efficiency. [Means for solving the problem]
[0005] The solar cell of the embodiment has a p-electrode, an n-electrode, a p-type light absorbing layer mainly made of a cuprous oxide compound provided on the p-electrode, an n-type layer provided between the p-type light absorbing layer and the n-electrode, and a compound of a first metal between the p-type light absorbing layer and the n-type layer. The coverage of the compound of the first metal on the p-type light absorbing layer is 10% or more and less than 100%. The first metal is one or more elements selected from the group consisting of Al, Hf, Zr, and B. The cuprous oxide compound is in direct contact with the compound of the first metal and the n-type layer. [Brief description of the drawings]
[0006] [Figure 1] FIG. 1 is a schematic cross-sectional view of a solar cell according to an embodiment. [Diagram 2] FIG. 2 is a diagram for explaining analysis spots of a solar cell according to an embodiment. [Diagram 3] FIG. 3 is a schematic diagram showing the distribution of a compound of a first metal according to an embodiment. [Figure 4] FIG. 4 is a schematic diagram showing the distribution of a compound of a first metal according to an embodiment. [Diagram 5] FIG. 5 is a schematic diagram showing the distribution of a compound of a first metal according to an embodiment. [Figure 6] FIG. 6 is a schematic diagram showing the distribution of a compound of a first metal according to an embodiment. [Figure 7] FIG. 7 is a cross-sectional view of a multi-junction solar cell according to an embodiment. [Figure 8] FIG. 8 is a perspective view of a solar cell module according to an embodiment. [Figure 9] FIG. 9 is a cross-sectional view of a solar cell module according to an embodiment. [Figure 10] FIG. 10 is a configuration diagram of a solar power generation system according to an embodiment. [Figure 11] FIG. 11 is a schematic diagram of a vehicle according to an embodiment. [Figure 12] FIG. 12 is a schematic diagram of a flying object according to an embodiment. [Figure 13] FIG. 13 is a table relating to an embodiment. [Figure 14] FIG. 14 is a table relating to an embodiment. [Figure 15] FIG. 15 is a table relating to an embodiment. [Figure 16] FIG. 16 is a table relating to an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] A preferred embodiment of the present invention will be described in detail below with reference to the drawings. Unless otherwise specified, the physical property values are shown at 25°C and 1 atmospheric pressure (atmosphere). The average indicates an arithmetic mean value. Each concentration is the average concentration of the target region or layer. In each layer, the inclusion of a specific element means, for example, an element whose presence is confirmed by SIMS (Secondary Ion Mass Spectrometry), and the absence of a specific element means, for example, an element whose presence cannot be confirmed by SIMS.
[0008] In the specification, " / " represents a division symbol. However, " / " in "or / and" means "or." In the specification, "·" represents a multiplication symbol. In the numerical values in the specification, "." represents a decimal point.
[0009] (First embodiment) The first embodiment relates to a solar cell. FIG. 1 shows a schematic cross-sectional view of a solar cell 100 of the first embodiment. As shown in FIG. 1, the solar cell 100 according to this embodiment has a substrate 1, a p-electrode 2 as a first electrode, a p-type light absorbing layer 3, an n-type layer 4, an n-electrode 5 as a second electrode, and a compound 6 of a first metal. An intermediate layer (not shown) may be included between the n-type layer 4 and the n-electrode 5. Sunlight may be incident from either the n-electrode 5 side or the p-electrode 2 side, but it is more preferable that it is incident from the n-electrode 5 side. The solar cell 100 of the embodiment is a transparent solar cell, so it is preferable to use it on the top cell side (light incident side) of a multi-junction solar cell. In FIG. 1, the substrate 1 is provided on the opposite side of the p-electrode 2 from the p-type light absorbing layer 3 side, but the substrate 1 may be provided on the opposite side of the n-electrode 5 from the n-type layer 4 side. The embodiment shown in FIG. 1 will be described below, but the embodiment in which the substrate 1 is provided on the n-electrode 5 side is similar except that the position of the substrate 1 is different. In the solar cell 100 of the embodiment, light is incident from the n-electrode 5 side toward the p-electrode 2 side.
[0010] When the solar cell 100 of the embodiment uses transmissive electrodes for the p-electrode 2 and n-electrode 5, it is a transmissive solar cell that has high transmittance for light in the wavelength band of 700 nm or more and 1200 nm or less, and is reddish (reddish brown), yellowish, or orange in color.
[0011] The substrate 1 is a transparent substrate. For the substrate 1, organic substrates such as light-transmitting acrylic, polyimide, polycarbonate, polyethylene terephthalate (PET), polypropylene (PP), fluorine-based resin (polytetrafluoroethylene (PTFE), perfluoroethylene propene copolymer (FEP), ethylene tetrafluoroethylene copolymer (ETFE), polychlorotrifluoroethylene (PCTFE), perfluoroalkoxyalkane (PFA), etc.), polyarylate, polysulfone, polyethersulfone, polyetherimide, etc., or inorganic substrates such as soda-lime glass, white plate glass, chemically strengthened glass, and quartz can be used. The substrate 1 may be a laminate of the substrates listed above.
[0012] The p-electrode 2 is provided on the substrate 1 and is disposed between the substrate 1 and the p-type light absorbing layer 3. The p-electrode 2 preferably forms an ohmic junction with the p-type light absorbing layer 3. The p-electrode 2 is a conductive layer having optical transparency provided on the p-type light absorbing layer 3 side. The thickness of the p-electrode 2 is typically 100 nm or more and 2000 nm or less. In FIG. 1, the p-electrode 2 is in direct contact with the p-type light absorbing layer 3. The p-electrode 2 preferably includes one or more layers of an oxide transparent conductive film. As the oxide transparent conductive film, a semiconductor conductive film such as indium tin oxide (ITO), aluminum doped zinc oxide (AZO), boron doped zinc oxide (BZO), gallium doped zinc oxide (GZO), doped tin oxide, titanium doped indium oxide (ITiO), indium zinc oxide (IZO), indium gallium zinc oxide (IGZO), hydrogen doped indium oxide (IOH) can be used, and is not particularly limited. The oxide transparent conductive film may be a laminated film having a plurality of films. The dopant for the tin oxide film is not particularly limited as long as it is one or more selected from the group consisting of In, Si, Ge, Ti, Cu, Sb, Nb, Ta, W, Mo, F, Cl, etc. The p electrode 2 preferably includes a tin oxide film doped with one or more elements selected from the group consisting of In, Si, Ge, Ti, Cu, Sb, Nb, Ta, W, Mo, F, Cl, etc. In the doped tin oxide film, it is preferable that one or more elements selected from the group consisting of In, Si, Ge, Ti, Cu, Sb, Nb, Ta, W, Mo, F, Cl, etc. are contained in an amount of 10 atomic % or less with respect to the tin contained in the tin oxide film. A laminated film in which an oxide transparent conductive film and a metal film are laminated can be used as the p electrode 2. The thickness of the metal film is preferably 1 [nm] or more and 2 [μm] or less, and the metal (including alloy) contained in the metal film is not particularly limited to Mo, Au, Cu, Ag, Al, Ta, W, etc.In addition, the p-electrode 2 preferably includes a dot-shaped, line-shaped or mesh-shaped electrode (one or more selected from the group consisting of metals, alloys, graphene, conductive nitrides and conductive oxides) between the oxide transparent conductive film and the substrate 1, or between the oxide transparent conductive film and the p-type light absorbing layer 3. The dot-shaped, line-shaped or mesh-shaped metal preferably has an aperture ratio of 50% or more with respect to the oxide transparent conductive film. The dot-shaped, line-shaped or mesh-shaped metal is not particularly limited to Mo, Au, Cu, Ag, Al, Ta, W, etc. When a metal film is used for the p-electrode 2, it is preferable to set the film thickness to about 5 [nm] or less from the viewpoint of transparency. When a line-shaped or mesh-shaped metal film is used, transparency is ensured at the openings, so the film thickness of the metal film is not limited to this.
[0013] A doped tin oxide film that forms an ohmic junction with the p-type light absorbing layer 3 is preferably provided on the outermost surface of the oxide transparent conductive film on the p-type light absorbing layer 3 side. It is preferable that at least a part of the doped tin oxide film provided on the outermost surface of the oxide transparent conductive film on the p-type light absorbing layer 3 side is in direct contact with the p-type light absorbing layer 3.
[0014] The p-type light absorbing layer 3 is a p-type semiconductor layer. The p-type light absorbing layer 3 is provided on the p-electrode 2. The p-type light absorbing layer 3 may be in direct contact with the p-electrode 2, or other layers may be present as long as electrical contact with the p-electrode 2 can be ensured. The p-type light absorbing layer 3 is disposed between the p-electrode 2 and the n-type layer 4. Not the entire surface of the p-type light absorbing layer 3 facing the n-type layer 4, but a part of the surface is in direct contact with the n-type layer 4. The p-type light absorbing layer 3 is mainly composed of a cuprous oxide compound. The cuprous oxide compound preferably has a cuprite structure.
[0015] The p-type light absorbing layer 3 is preferably a semiconductor layer containing a cuprous oxide compound. The p-type light absorbing layer 3 is preferably a polycrystal of a cuprous oxide compound. The p-type light absorbing layer 3 contains copper (Cu), copper oxide (CuO), and copper hydroxide (Cu(OH)) as impurities. 2 ) may contain a trace amount of one or more cuprous oxide impurities selected from the group consisting of:
[0016] When all elements except for oxygen contained in the p-type light absorbing layer 3 are taken as 100[%], the copper element contained in the p-type light absorbing layer 3 is preferably 90[%] or more and 100[%] or less, preferably 95[%] or more and 100[%] or less, more preferably 98[%] or more and 100[%] or less, and even more preferably 99[%] or more and 100[%] or less.
[0017] In the case where the cuprous oxide compound contains elements other than copper and oxygen, when all elements except the oxygen element contained in the p-type light absorbing layer 3 are taken as 100%, the copper element contained in the p-type light absorbing layer 3 is preferably 90% or more and 99.9% or less, preferably 95.0% or more and 99.9% or less, more preferably 98% or less and 99.9% or less, and even more preferably 99.0% or more and 99.9% or less.
[0018] The cuprous oxide compound contains copper and oxygen, and further contains an element represented by M1. The element represented by M1 is preferably one or more elements selected from the group consisting of Cl, F, Br, I, Sn, Sb, Ag, Li, Na, K, Cs, Rb, Al, In, Zn, Mg, Ga, Si, Ge, N, P, B, Ti, Hf, Zr, and Ca.
[0019] When all elements except for oxygen contained in the p-type light absorbing layer 3 are taken as 100[%], the total of the copper element and the element represented by M1 contained in the p-type light absorbing layer 3 is preferably 95[%] or more and 100[%] or less, more preferably 98[%] or more and 100[%] or less, and even more preferably 99[%] or more and 100[%] or less.
[0020] The number of oxygen atoms contained in the cuprous oxide compound is preferably 0.48 or more and 0.56 or less, assuming that the number of copper atoms is 1. If the amount of oxygen is large relative to the amount of copper, the ratio of copper oxide contained in the cuprous oxide compound increases, narrowing the band gap and decreasing the light transmittance of the p-type light absorbing layer 3, which is not preferable. If the amount of oxygen is small relative to the amount of copper, the amount of copper contained in the cuprous oxide compound increases, which is not preferable, as it decreases the light transmittance. Furthermore, if the ratio of oxygen to copper does not satisfy the above range, it becomes difficult for the cuprous oxide compound to have a cuprite structure.
[0021] Preferably, 95 wt% to 100 wt% of the p-type light absorbing layer 3 is a cuprous oxide compound, more preferably, 98 wt% to 100 wt% of the p-type light absorbing layer 3 is a cuprous oxide compound, and even more preferably, 99 wt% to 100 wt% of the p-type light absorbing layer 3 is a cuprous oxide compound. 100 wt% of the p-type light absorbing layer 3 can be composed of a cuprous oxide compound.
[0022] It is preferable that the p-type light absorbing layer 3 contains few heterogeneous phases and has good crystallinity, because this increases the light transmittance of the p-type light absorbing layer 3. The band gap of the p-type light absorbing layer 3 can be adjusted by, for example, including an element other than Cu and O in the p-type light absorbing layer 3. The band gap of the p-type light absorbing layer 3 is preferably 2.0 [eV] or more and 2.2 [eV] or less. With a band gap in this range, in a multi-junction solar cell in which a solar cell using Si as a light absorbing layer is used as a bottom cell and the solar cell of the embodiment is used as a top cell, sunlight can be efficiently utilized in both the top cell and the bottom cell. The p-type light absorbing layer 3 preferably contains Sn and / or Sb. The Sn and Sb in the p-type light absorbing layer 3 may be added to the p-type light absorbing layer 3 or may be derived from the p-electrode 2. The Ga contained in the p-type light absorbing layer 3 is not included in the raw material for forming the p-type light absorbing layer 3, and is Ga contained in the n-type layer 4 diffused into the p-type light absorbing layer 3. When other elements are used during deposition of the n-type layer 4, these elements may also diffuse into the p-type light absorbing layer 3.
[0023] The above composition ratio of the p-type light absorbing layer 3 is the composition ratio of the entire p-type light absorbing layer 3. In addition, the above compound composition ratio of the p-type light absorbing layer 3 is preferably satisfied in the p-type light absorbing layer 3 as a whole.
[0024] The p-type light absorbing layer 3 preferably has ap+ type (p plus type) region on the p-electrode 2 side.
[0025] The p-type light absorbing layer 3 preferably has a p-type (p minus type) region on the n-type layer side. The p-type light absorbing layer 3 preferably has a p-type (p minus type) region on the n-type layer side and a p+ type (p plus type) region on the p-electrode 2 side.
[0026] When elements of the n-type layer 4 diffuse into the p-type light absorbing layer 3 and / or the p-type light absorbing layer 3 diffuse into the n-type layer 4, a mixed region having a thickness of 20 [nm] or less may exist between the p-type light absorbing layer 3 and the n-type layer 4 where the elements of each other are diffused. 90 [atom%] or less of the metal elements in the mixed region are the metals contained in the p-type light absorbing layer 3, and further, 10 [atom%] or more of the metal elements in the mixed region are the metal elements contained in the n-type layer 4. When a mixed region exists, the surface of the p-type light absorbing layer 3 including the mixed region on the n-type layer 4 side is based on the position of the surface of the compound 6 of the first metal on the p-electrode 2 side.
[0027] The thickness of the p-type light absorbing layer 3 is determined by cross-sectional observation using an electron microscope or a step gauge, and is preferably 2000 [nm] to 15000 [nm] (2 [μm] to 15 [μm]), more preferably 2500 [nm] to 10000 [nm], even more preferably 4000 [nm] to 10000 [nm], and preferably 4000 [nm] to 8000 [nm]. The p-type light absorbing layer 3 has a small unevenness on the surface, and the difference between the minimum thickness and the maximum thickness of the p-type light absorbing layer 3 is preferably 0 [nm] to 100 [nm], more preferably 0 [nm] to 50 [nm]. The p-type light absorbing layer 3 has a rectangular parallelepiped shape.
[0028] The composition analysis of the p-type light absorbing layer 3 and the like can be performed, for example, by analyzing analysis spots (A1 to A9) that are distributed as closely as possible at equal intervals as shown in the diagram explaining the analysis spots in FIG. 2, for example, by secondary ion mass spectrometry (SIMS). FIG. 2 is a schematic diagram of a solar cell 100 viewed from the light incident side. When analyzing the composition of the p-type light absorbing layer 3, D1 is the length of the p-type light absorbing layer 3 in the width direction, and D2 is the length of the p-type light absorbing layer 3 in the depth direction. The composition analysis is performed, for example, from the surface of the n-type layer 4 toward the p-electrode 2.
[0029] The composition of the p-type light absorbing layer 3 is determined by setting the thickness of the p-type light absorbing layer 3 to d 1 In this case, 0.1d from the surface of the p-type light absorbing layer 3 on the p-electrode 2 side 1 , 0.2d 1 , 0.3d 1 , 0.4d 1 , 0.5d 1 , 0.6d 1 , 0.7d 1 , 0.8d 1 , 0.9d 1 In the case of SIMS, the elements of the n-type layer 4 are easily detected when the surface of the p-type light absorbing layer 3 is analyzed, so the average value of the composition at a depth of 0.1d 1 It is preferable to obtain the average composition by analyzing the p-type absorber layer 3 from each point.
[0030] The p-type light absorbing layer 3 is preferably formed by, for example, a sputtering method. Specifically, the member on which the p-electrode 2 is formed on the substrate 1 is heated to 300°C or more and 600°C or less, and the oxygen partial pressure is preferably within the range of 0.01 Pa or more and 4.8 Pa or less and within the range of 0.02 μm / min or more and 20 μm / min or less. From the viewpoint of forming a polycrystalline film with high transparency and large grain size, it is more preferable that the oxygen partial pressure is 0.55xd [Pa] or more and 1.00xd [Pa] or less when the deposition rate is d. In addition, the heating temperature is more preferably 350°C or more and 500°C or less. An element M1 can be added during film formation. After the formation of the p-type light absorbing layer 3, a treatment may be performed to oxidize the surface on the side on which the compound 6 of the first metal and the n-type layer 4 are formed.
[0031] The n-type layer 4 is an n-type semiconductor layer. The n-type layer 4 is disposed between the p-type light absorbing layer 3 and the n-electrode 5. The n-type layer 4 is preferably provided on the p-type light absorbing layer 3. The n-type layer 4 is formed by, for example, an ALD method.
[0032] The n-type layer 4 preferably contains a compound (oxide) mainly composed of Ga. The n-type layer 4 may be an oxide mainly composed of Ga mixed with other oxides, an oxide mainly composed of Ga doped with other elements, or an oxide mainly composed of Ga doped with other elements may be mixed with other oxides. The n-type layer 4 is a single layer or a multilayer. Of the metal elements contained in the n-type layer 4, Ga is preferably 40 atomic % or more, more preferably 50 atomic % or more. The metal elements including Ga contained in the n-type layer 4 may be inclined from the p-type light absorbing layer 3 side to the n-electrode 5 side. When the n-type layer 4 is a multilayer semiconductor layer (for example, two layers), it is called a first n-type layer and a second n-type layer from the p-type light absorbing layer 3 side. The element represented by M2 contained in the first n-type layer is preferably less than the element represented by M2 contained in the second n-type layer.
[0033] The n-type layer 4 preferably contains an oxide containing an element represented by M2 and Ga. The oxide mainly containing Ga is, for example, an oxide containing an element represented by M2 and Ga. The n-type layer 4 preferably contains an oxide containing M2, which is one or more elements selected from the group consisting of H, Sn, Sb, Cu, Ag, Li, Na, K, Cs, Rb, Al, In, Zn, Mg, Si, Ge, N, B, Ti, Hf, Zr, Ca, Ce, La, Pr, and Nd, and Ga. The n-type layer 4 preferably contains 90 wt% or more and 100 wt% or less of an oxide containing M2, which is one or more elements selected from the group consisting of H, Sn, Sb, Cu, Ag, Li, Na, K, Cs, Rb, Al, In, Zn, Mg, Si, Ge, N, B, Ti, Hf, Zr, Ca, Ce, La, Pr, and Nd, and Ga. The compound mainly containing Ga in the n-type layer 4 has an average composition of Ga. h1 M2 i1 O j1 It is preferable that h1, i1, and j2 satisfy 1.8≦h1≦2.1, 0≦i1≦0.2, and 2.9≦j1≦3.1.
[0034] It is preferable that 90 [wt%] or more and 100 [wt%] or less of the n-type layer 4 is an oxide containing M2 and Ga. It is more preferable that 95 [wt%] or more and 100 [wt%] or less of the n-type layer 4 is an oxide containing M2 and Ga. It is even more preferable that 98 [wt%] or more and 100 [wt%] or less of the n-type layer 4 is a compound represented by an oxide containing M2 and Ga. The Cu contained in the n-type layer 4 is not contained in the raw material for forming the n-type layer 4, but is Cu contained in the p-type light absorbing layer 3 that has diffused into the n-type layer 4. If other elements are also used when forming the p-type light absorbing layer 3, these elements may also diffuse into the n-type layer 4.
[0035] The thickness of the n-type layer 4 is typically 3 nm or more and 100 nm or less. If the thickness of the n-type layer 4 is less than 3 nm, leakage current may occur when the coverage of the n-type layer 4 is poor, resulting in a deterioration of characteristics. If the coverage is good, the thickness is not limited to the above. If the thickness of the n-type layer 4 exceeds 50 nm, the resistance of the n-type layer 4 may become excessively high, resulting in a deterioration of characteristics, and a decrease in short-circuit current may occur due to a decrease in transmittance. Therefore, the thickness of the n-type layer 4 is more preferably 3 nm or more and 20 nm or less, and even more preferably 5 nm or more and 20 nm or less.
[0036] The composition of the compound in the n-type layer 4 is the average composition of the entire n-type layer 4 unless otherwise specified. 4 In this case, 0.2d from the surface of the n-type layer 4 on the p-type light absorbing layer 3 side 4 , 0.5d 4 , 0.8d 4 The average value of the composition at a depth of 100 nm is the average value of the composition at a depth of 100 nm. Except for the condition that the element composition ratio of the compound of the n-type layer 4 is inclined, the n-type layer 4 preferably satisfies the above and following preferred compositions at each depth. When the n-type layer 4 is very thin (for example, 5 nm or less), the composition at a depth of 0.5d from the surface of the n-type layer 4 on the p-type light absorbing layer 3 side can be regarded as the composition of the entire n-type layer 4. The analysis is performed by analyzing the analysis spots (A1 to A9) distributed at each distance from the surface of the n-type layer 4 as equally spaced as possible as shown in the diagram explaining the analysis spots in FIG. 3 by, for example, secondary ion mass spectrometry (SIMS). FIG. 3 is a schematic diagram of the solar cell 100 as seen from the light incident side. When analyzing the composition of the n-type layer 4, D1 is the length in the width direction of the n-type layer 4, and D2 is the length in the depth direction of the n-type layer 4.
[0037] The average composition of the region from the surface (starting point) of the n-type layer 4 on the p-type light absorbing layer 3 side to the n-electrode 5 side is Ga h2 M3 i2 O j2It is represented by the formula: h2, i2 and j2 preferably satisfy 1.8≦h2≦2.1, 0.00≦i2≦0.05 and 2.9≦j2≦3.1, more preferably satisfy 1.8≦h2≦2.1, 0.00≦i2≦0.03 and 2.9≦j2≦3.1, and even more preferably satisfy 1.8≦h2≦2.1, 0.00≦i2≦0.01 and 2.9≦j2≦3.1. The element represented by M3 is preferably one or more elements selected from the group consisting of H, Sn, Sb, Cu, Ag, Li, Na, K, Cs, Rb, Al, In, Zn, Mg, Si, Ge, N, B, Ti, Hf, Zr, Ca, Ce, La, Pr and Nd. The element represented by M3 is preferably one or more elements selected from the group consisting of H, Sn, Sb, Cu, Ag, Li, Na, K, Cs, Rb, In, Zn, Mg, Si, Ge, N, Ti, Ca, Ce, La, Pr, and Nd. In a region from the surface (starting point) of the n-type layer 4 on the p-type light absorbing layer 3 side to 1 [nm] toward the n-electrode 5 side, it is preferable that 1.8≦h2≦2.i2=0 and 2.9≦j2≦3.1 are satisfied.
[0038] Between the p-type light absorbing layer 3 and the n-type layer 4, a compound 6 of the first metal is provided. The cuprous oxide compound is preferably in direct contact with the compound 6 of the first metal and the n-type layer 4. The compound 6 of the first metal is preferably distributed in an island shape between the p-type light absorbing layer 3 and the n-type layer 4. The surface of the compound 6 of the first metal facing the p-type light absorbing layer 3 is more preferably in direct contact with the p-type light absorbing layer 3. The surface of the compound 6 of the first metal other than the surface facing the p-type light absorbing layer 3 is more preferably in direct contact with the n-type layer 4. The coverage of the compound 6 of the first metal covering the p-type light absorbing layer 3 (the area of the compound 6 of the first metal in contact with the p-type light absorbing layer 3 relative to the area of the surface of the p-type light absorbing layer 3 on the n-type layer 4 side) is preferably 10% or more and less than 100%. In other words, the compound 6 of the first metal has a side surface. The side surfaces of the compound 6 of the first metal are preferably in direct contact with the p-type light absorbing layer 3 and / or the n-type layer 4. In the portion where the compound 6 of the first metal is not present, the p-type light absorbing layer 3 and the n-type layer 4 are in direct contact with each other.
[0039] The compound 6 of the first metal is preferably present so as to spread in the surface direction of the p-type light absorbing layer 3 on the n-type layer 4 side. The compound 6 of the first metal is preferably not contained inside the p-type light absorbing layer 3 or inside the n-type layer 4. In other words, the compound 6 of the first metal that is not in contact with the surface of the p-type light absorbing layer 3 is preferably not present in the solar cell 100. In other words, the compound 6 of the first metal that is not in contact with the surface of the n-type layer 4 is preferably not present in the solar cell 100.
[0040] The compound 6 of the first metal is preferably an insulator. The compound 6 of the first metal is an insulating material in the stacking direction (the stacking direction of the p-type light absorbing layer 3 and the n-type layer 4). The compound 6 of the first metal is preferably an oxide, nitride or sulfide of the first metal. The compound 6 of the first metal is preferably composed of an oxide, nitride or sulfide of the first metal. Since the compound 6 of the first metal exists in an extremely small region, if the compound 6 of the first metal is an oxide, it is difficult to determine whether the oxygen at the end of the region where the compound 6 of the first metal exists is regarded as the oxygen of the n-type layer 4 or the oxygen of the compound 6 of the first metal. Therefore, when expressing the composition of the compound 6 of the first metal in the embodiment and the example, the composition is expressed in the following numerical range.
[0041] The compound 6 of the first metal is more preferably an oxide of the first metal.The compound 6 of the first metal is preferably composed of an oxide of the first metal.
[0042] The first metal element is preferably one or more elements selected from the group consisting of Al, Hf, Zr, and B. The first metal element is preferably Al, Hf, Zr, or B.
[0043] The first metal compound 6 is Al x1 Hf x2 Zr x3 B x4 O yIt is preferable that x1, x2, x3, x4 and y satisfy 0.8≦x1+x2+x3+x4≦1.2 and 0.3≦(x1+x2+x3+x4) / y≦0.8, more preferably 0.9≦x1+x2+x3+x4≦1.1 and 0.4≦(x1+x2+x3+x4) / y≦0.7, and further more preferably 0.95≦x1+x2+x3+x4≦1.05 and 0.6≦(x1+x2+x3+x4) / y≦0.7.
[0044] Compound 6 of the first metal is Al x1 Hf x2 Zr x3 B x4 O y In the compound represented by the formula (I), when the compound 6 of the first metal is mainly composed of Al, it is preferable that 0.8≦x1 / (x1+x2+x3+x4)≦1 is satisfied, and it is more preferable that 0.9≦x1 / (x1+x2+x3+x4)≦1 is satisfied.
[0045] The first metal compound 6 is Al x1 O y It is preferable that the compound 6 of the first metal is a compound represented by the formula: x1 O y In the case of a compound represented by the formula (I), it is preferable that 0.5≦x1 / y≦0.8 is satisfied, and it is more preferable that 0.6≦x1 / y≦0.7 is satisfied.
[0046] Compound 6 of the first metal is Al x1 Hf x2 Zr x3 B x4 O y In the compound represented by the formula (I) and the first metal compound 6 is mainly composed of Hf, it is preferable that 0.8≦x2 / (x1+x2+x3+x4)≦1 is satisfied, and it is more preferable that 0.9≦x2 / (x1+x2+x3+x4)≦1 is satisfied.
[0047] The first metal compound 6 is Hf x2 O y It is preferable that the compound 6 of the first metal is a compound represented by the formula: x2 O yIn the case of a compound represented by the formula (I), it is preferable that 0.3≦x2 / y≦0.7 is satisfied, and it is more preferable that 0.4≦x2 / y≦0.6 is satisfied.
[0048] Compound 6 of the first metal is Al x1 Hf x2 Zr x3 B x4 O y In the compound represented by the formula (I), when the compound 6 of the first metal is mainly composed of Zr, it is preferable that 0.8≦x3 / (x1+x2+x3+x4)≦1 is satisfied, and it is more preferable that 0.9≦x3 / (x1+x2+x3+x4)≦1 is satisfied.
[0049] The first metal compound 6 is Zr x3 O y It is preferable that the compound 6 of the first metal is a compound represented by the formula: x3 O y In the case of a compound represented by the formula (I), it is preferable that 0.3≦x3 / y≦0.7 is satisfied, and it is more preferable that 0.4≦x3 / y≦0.6 is satisfied.
[0050] Compound 6 of the first metal is Al x1 Hf x2 Zr x3 B x4 O y In the compound represented by the formula (I), when the compound 6 of the first metal is mainly composed of B, it is preferable that 0.8≦x4 / (x1+x2+x3+x4)≦1 is satisfied, and it is more preferable that 0.9≦x4 / (x1+x2+x3+x4)≦1 is satisfied.
[0051] The compound 6 of the first metal is B x4 O y It is preferable that the compound 6 of the first metal is a compound represented by the formula: x4 O y In the case of a compound represented by the formula (I), it is preferable that 0.5≦x4 / y≦0.8 is satisfied, and it is more preferable that 0.6≦x4 / y≦0.7 is satisfied.
[0052] The compound 6 of the first metal used in the examples also satisfies the above-mentioned preferable conditions of x1, x2, x3, x4 and y.
[0053] When the first metal compound 6 is present between the p-type light absorbing layer 3 and the n-type layer 4 with a coverage rate of less than 100%, a high curvature factor (FF) and a high open circuit voltage (Voc) can be achieved at the same time, which contributes to improving the conversion efficiency of the solar cell.
[0054] Compared to a solar cell configured so that the compound of the first metal 6 is not present, oxygen in the cuprous oxide compound on the surface of the p-type light absorbing layer 3 of the embodiment is less likely to be extracted by the n-type layer 4. Therefore, even if defects are present on the surface of the p-type light absorbing layer 3, the number of such defects will be smaller than in a solar cell configured so that the compound of the first metal 6 is not present, which is considered to contribute to improved conversion efficiency.
[0055] It is believed that oxygen in the cuprous oxide compound is easily extracted by the n-type layer 4, but the provision of the compound of the first metal 6 suppresses the extraction of oxygen from the cuprous oxide compound. When the n-type layer 4 having a thickness greater than that of the compound of the first metal 6 is formed after the compound of the first metal 6 is formed, the compound of the first metal 6 becomes highly stable, and a part of the surface of the p-type light absorbing layer 3 is covered with the compound of the first metal 6, which suppresses the n-type layer 4 from extracting oxygen from the cuprous oxide compound. In this way, the n-type layer 4 can be formed while suppressing the formation of surface defects in the formed cuprous oxide compound.
[0056] If the thickness of the compound 6 of the first metal is large, it becomes difficult to extract the photocarriers generated in the light absorption layer 3 to the n-type layer 4, so the average thickness of the compound 6 of the first metal is preferably 0.2 nm to 1 nm (approximately the thickness of one atomic layer). From the same viewpoint, the maximum thickness of the compound 6 of the first metal is preferably 0.2 nm to 1 nm, more preferably 0.4 nm to 0.8 nm. The thickness of the compound 6 of the first metal is obtained by observing the same spots as A1 to A9 with a TEM (transmission electron microscope) at a high magnification (for example, 1 million times).
[0057] Considering the transmittance of the solar cell 100, the compound 6 of the first metal is preferably a wide gap that satisfies the above thickness. Therefore, the band gap of the compound 6 of the first metal is preferably 5 eV or more and 10 eV or less, and more preferably 6 eV or more and 9 eV or less.
[0058] In the portion where the compound 6 of the first metal is present on the p-type light absorbing layer 3, a pattern in which the first metal and oxygen are bonded is preferably repeated. In the portion where the compound 6 of the first metal is not present on the p-type light absorbing layer 3, when the n-type layer 4 contains gallium and oxygen, a pattern in which gallium and oxygen are bonded is preferably repeated. When the pattern in which the first metal, oxygen, and gallium are bonded is repeated randomly without any regularity overall, the oxide layer formed on the p-type light absorbing layer 3 is an oxide of Ga and Al, which is different from the configuration of the embodiment.
[0059] A passivation film is sometimes used between the pn interface of a solar cell, and the passivation film is, for example, 3 [nm] thick or more. Such a thick film may be formed on a CIGS film having a chalcopyrite structure, but if the CIGS film has a chalcopyrite structure, the solar cell of the embodiment does not suffer from deterioration in characteristics due to the use of a first metal compound 6 that is thick enough not to satisfy the above range due to differences in the constituent elements including the composition ratio. However, when a passivation film having a thickness of 3 [nm] or more is used in other solar cells including a CIGS film, it is difficult to form the passivation film by using a Cu 2 It was found that when the compound 6 of the first metal is used between the p-type light absorbing layer 3 and the n-type layer 4 of an O solar cell, the transmittance is good, but Jsc, Voc, FF, and conversion efficiency are all significantly reduced. The compound 6 of the first metal is intentionally opened (coverage rate is less than 100%), and its thickness is very thin, which is different from a passivation film. In addition, since the purpose is only to suppress the extraction of oxygen from the light absorbing layer 3 by the n-type layer 4, the compound 6 of the first metal may be extremely thin.
[0060] From the above viewpoint, the coverage is more preferably 10% or more and less than 100%, more preferably 20% or more and 80% or less, and more preferably 30% or more and 60% or less. When the amount of the compound 6 of the first metal provided on the p-type light absorbing layer 3 increases, the FF gradually decreases, and when it substantially exceeds one atomic layer, the Jsc also decreases. When the compound 6 of the first metal provided on the p-type light absorbing layer 3 is about two atomic layers, although the Voc is high, the Jsc and FF decrease significantly, and the conversion efficiency decreases. In addition, even if the thickness of the compound 6 of the first metal is sufficiently thin, if the coverage is low, the Voc does not substantially improve, so the coverage is preferably 10% or more. The coverage and the composition of the compound 6 of the first metal are obtained by removing the n-electrode 5 of the solar cell 100 by ion milling or the like and analyzing it from the n-type layer 4 side by HAXPES (hard X-ray photoelectron spectroscopy).
[0061] The compound 6 of the first metal is preferably formed on the p-type light absorbing layer 3 by, for example, an ALD method. The n-type layer 4 is preferably formed on the p-type light absorbing layer 3 having the compound 6 of the first metal formed on a portion of the surface.
[0062] The compound used when forming the first metal compound 6 by the ALD method is preferably one or more selected from the group consisting of trimethylaluminum, triethylaluminum, trisdimethylamidoaluminum, triethoxyaluminum, tetrakisdimethylaminohafnium, tetrakisethylmethylaminohafnium, tetrakisdiethylaminohafnium, tetrakisdimethylaminozirconium, tetrakisethylmethylaminozirconium, tetrakisdiethylaminozirconium, triethylboron, and trisdimethylaminoborane. When forming the first metal compound 6 by the ALD method, it is preferable to adjust the pulse irradiation time, etc., to form the first metal compound 6 of 1 nm or less, for example, less than one atomic layer, on the entire surface of the p-type light absorbing layer 3 on the side where the n-type layer 4 is formed.
[0063] 3 to 6 show schematic diagrams of the distribution of the compounds 6 of the first metal. As shown in the figures, the form of the distribution of the compounds 6 of the first metal is not particularly limited. Although it is preferable that the compounds 6 of the first metal have a high dispersibility, the compounds 6 of the first metal that are biased as shown in FIG. 3 also contribute to improving the conversion efficiency. As shown in the figures, the island-like distribution is interpreted in a broad sense. The average area of the islands of the compounds 6 of the first metal is, for example, preferably 3% or more and less than 100% of the area of the surface of the p-type light absorbing layer 3 on the n-type layer 4 side, more preferably 5% or more and 90% or less, and even more preferably 10% or more and 90% or less.
[0064] The n-electrode 5 is an electrode on the n-type layer 4 side, which has optical transparency to visible light. The n-electrode 5 is preferably provided on the n-type layer 4. The n-electrode 5 and the p-type light absorbing layer 3 sandwich the n-type layer 4 and the compound 6 of the first metal. An intermediate layer (not shown) can be provided between the n-type layer 4 and the n-electrode 5. The n-electrode 5 is preferably an oxide transparent conductive film. The oxide transparent conductive film used in the n-electrode 5 is preferably one or more semiconductor conductive films selected from the group consisting of indium tin oxide, aluminum doped zinc oxide, boron doped zinc oxide, gallium doped zinc oxide, indium doped zinc oxide, titanium doped indium oxide, indium gallium zinc oxide, and hydrogen doped indium oxide. The dopant for the tin oxide film is not particularly limited as long as it is one or more selected from the group consisting of In, Si, Ge, Ti, Cu, Sb, Nb, Ta, W, Mo, F, Cl, etc. The n-electrode 5 may include a mesh or line-shaped electrode in order to reduce the resistance of the oxide transparent conductive film. The mesh or line-shaped electrode may be made of any material, including, but not limited to, Mo, Au, Cu, Ag, Al, Ta, or W. Graphene may also be used for the n-electrode 5. Graphene is preferably laminated with silver nanowires.
[0065] The thickness of n-electrode 5 is determined by cross-sectional observation using an electron microscope or a step gauge, and is not particularly limited, but is typically 50 nm or more and 2 μm or less.
[0066] The n-electrode 5 is preferably formed by, for example, ALD or sputtering.
[0067] Second embodiment The second embodiment relates to a multi-junction solar cell. Fig. 7 shows a cross-sectional conceptual diagram of a multi-junction solar cell of the second embodiment. The multi-junction solar cell 200 of Fig. 7 has the solar cell (first solar cell) 100 of the first embodiment and a second solar cell 201 on the light incident side. The band gap of the light absorption layer of the second solar cell 201 is smaller than the band gap of the p-type light absorption layer 3 of the solar cell 100 of the first embodiment. The multi-junction solar cell 200 of the embodiment also includes a solar cell in which three or more solar cells are joined together.
[0068] Since the band gap of the p-type light absorbing layer (cuprous oxide) 3 of the first solar cell 100 of the first embodiment is about 2.0 eV or more and 2.2 eV or less, the band gap of the light absorbing layer of the second solar cell 201 is preferably 1.0 eV or more and 1.6 eV or less. The light absorbing layer of the second solar cell 201 is preferably one or more compound semiconductor layers selected from the group consisting of CIGS and CdTe with a high In content, crystalline silicon, and a perovskite compound.
[0069] Third embodiment The third embodiment relates to a solar cell module. Fig. 8 shows a perspective view of a solar cell module 300 of the third embodiment. The solar cell module 300 in Fig. 8 is a solar cell module in which a first solar cell module 301 and a second solar cell module 302 are stacked. The first solar cell module 301 is on the light incident side, and uses the solar cell 100 of the first embodiment. It is preferable to use the second solar cell 201 for the second solar cell module 302.
[0070] FIG. 9 shows a cross-sectional view of a solar cell module 300. FIG. 9 shows the structure of the first solar cell module 301 in detail, but does not show the structure of the second solar cell module 302. For the second solar cell module 302, the structure of the solar cell module is appropriately selected depending on the light absorption layer of the solar cell to be used. The solar cell module 300 in FIG. 9 includes a plurality of submodules 303 surrounded by dashed lines in which a plurality of solar cells 100 (solar cells) are arranged in the horizontal direction and electrically connected in series by wiring 304, and the plurality of submodules 303 are electrically connected in parallel or in series. Adjacent submodules 303 are electrically connected by bus bars 305.
[0071] Adjacent solar cells 100 have their n-electrodes 5 on the upper side and p-electrodes 2 on the lower side connected by wiring 304. The solar cell 100 of the third embodiment has a substrate 1, a p-electrode 2, a p-type light absorbing layer 3, an n-type layer 4, and an n-electrode 5, similar to the solar cell 100 of the first embodiment. Both ends of the solar cell 100 in the submodule 303 are connected to a bus bar 305, and the bus bar 305 is preferably configured to electrically connect the multiple submodules 303 in parallel or series and adjust the output voltage with the second solar cell module 302. Note that the connection form of the solar cells 100 shown in the third embodiment is an example, and a solar cell module can be configured by other connection forms.
[0072] (Fourth embodiment) The fourth embodiment relates to a solar power generation system. The solar cell module of the fourth embodiment can be used as a generator that generates power in the solar power generation system of the fourth embodiment. The solar power generation system of the embodiment generates power using a solar cell module, and specifically includes a solar cell module that generates power, a means for converting the generated electricity, and a storage means for storing the generated electricity or a load for consuming the generated electricity. FIG. 10 shows a configuration diagram of a solar power generation system 400 of the embodiment. The solar power generation system of FIG. 10 includes a solar cell module 401 (300), a converter 402, a storage battery 403, and a load 404. Either the storage battery 403 or the load 404 may be omitted. The load 404 may be configured to be able to utilize the electrical energy stored in the storage battery 403. The converter 402 is a device including a circuit or element that performs power conversion such as voltage transformation and DC-AC conversion, such as a DC-DC converter, a DC-AC converter, or an AC-AC converter. The converter 402 may have a suitable configuration depending on the generated voltage and the configurations of the storage battery 403 and the load 404 .
[0073] The solar cell included in the submodule 303 that receives light in the solar cell module 40100 generates electricity, and the electric energy is converted by the converter 402 and stored in the storage battery 403 or consumed by the load 404. It is preferable to provide the solar cell module 401 with a solar tracking drive device for always directing the solar cell module 401 toward the sun, a collector for collecting sunlight, or a device for improving power generation efficiency.
[0074] The solar power generation system 400 is preferably used in real estate such as residences, commercial facilities, and factories, and in movable property such as vehicles, aircraft, and electronic devices. By using the solar cell with excellent conversion efficiency of the embodiment in a solar cell module, an increase in the amount of power generation is expected.
[0075] A vehicle is shown as an example of the use of the solar power generation system 400. FIG. 11 shows a schematic diagram of the vehicle 500. The vehicle 500 in FIG. 11 has a vehicle body 501, a solar cell module 502, a power converter 503, a storage battery 504, a motor 505, and tires (wheels) 506. Electric power generated by the solar cell module 502 provided on the upper part of the vehicle body 501 is converted by the power converter 503 and charged in the storage battery 504, or the electric power is consumed by a load such as the motor 505. The vehicle 500 can be moved by rotating the tires (wheels) 506 by the motor 505 using the electric power supplied from the solar cell module 502 or the storage battery 504. The solar cell module 502 may not be of a multi-junction type, but may be composed of only a first solar cell module equipped with the solar cell 100 of the first embodiment. When a transparent solar cell module 502 is adopted, it is also preferable to use the solar cell module 502 as a window for generating electricity on the side of the vehicle body 501 in addition to the upper part of the vehicle body 501.
[0076] An air vehicle (drone) is shown as an example of use of the solar power generation system 400. The air vehicle uses a solar cell module 401. The configuration of the air vehicle according to this embodiment will be briefly described using the schematic diagram of the air vehicle 600 in FIG. 12. The air vehicle 600 has a solar cell module 401, a body frame 601, a motor 602, a rotor 603, and a control unit 604. The solar cell module 401, the motor 602, the rotor 603, and the control unit 604 are arranged on the body frame 601. The control unit 604 converts the power output from the solar cell module 401 and adjusts the output. The motor 602 rotates the rotor 603 using the power output from the solar cell module 401. By making the air vehicle 600 of this configuration having the solar cell module 401 of the embodiment, a air vehicle that can fly using more power is provided. The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.
[0077] Example A (Example A1) On the glass substrate 1, ITO (In:Sn=80:20, thickness 150 [nm]) and ATO (Sn:Sb=98:2, thickness 100 [nm]) are deposited on the top surface of the glass substrate 1 as a p-electrode 2 on the back side. A 6 [μm] thick Cu layer is deposited on the ATO as a p-type light absorbing layer 3 by sputtering in an oxygen and argon gas atmosphere. 2 After the p-type light absorbing layer 3 is formed, a thin Al layer is formed as the compound 6 of the first metal by the ALD method. x1 O y Then, a 10 nm thick Ga layer is formed as the n-type layer 4. 2 O 3 Then, a 0.1 μm-thick AZO(ZnO:Al) film is formed as the n-electrode 5, thereby completing the solar cell 100.
[0078] A solar simulator that mimics an AM1.5G light source is used, and a reference Si cell is used under that light source, with the amount of light adjusted to 1 sun. Measurements are taken at atmospheric pressure with the temperature in the measurement room at 25°C. The voltage is swept and the short-circuit current density Jsc (current divided by cell area) is measured. With the horizontal axis representing voltage and the vertical axis representing current density, the point where they intersect is the open-circuit voltage Voc. On the measurement curve, the voltage and short-circuit current density are multiplied together, and the maximum points are designated as Vmpp and Jmpp (maximum power point), respectively, and the fill factor can be calculated from FF = (Vmpp * Jmpp) / (Voc * Jsc). Conversion efficiency can be calculated from Eff. = Voc * Jsc * FF.
[0079] Regarding light transmittance, a light transmittance of 75% or more for the wavelength band of 700 nm or more and 1000 nm or less is evaluated as A, a light transmittance of 70% or more and less than 75% for the wavelength band of 700 nm or more and 1000 nm or less is evaluated as B, and a light transmittance of less than 70% for the wavelength band of 700 nm or more and 1000 nm or less is evaluated as C.
[0080] If the Jsc is 1.05 times or more the conversion efficiency of the comparison target, it is rated as A, if it is 1.0 times or more but less than 1.05 times the Jsc of comparison target 1, it is rated as B, and if it is less than 1.0 times the Jsc of comparison target 1, it is rated as C.
[0081] When Voc is 1.05 times or more the conversion efficiency of comparison 1, it is rated as A. When it is 1.00 times or more but less than 1.05 times the Voc of comparison 1, it is rated as B. When it is less than 1.00 times the Voc of comparison 1, it is rated as C.
[0082] FF is rated as A if its conversion efficiency is 1.01 times or more than that of comparison object 1, as B if its conversion efficiency is 0.98 times or more but less than 1.01 times that of comparison object 1, and as C if its conversion efficiency is less than 0.98 times that of comparison object 1.
[0083] Conversion efficiency is rated as A when it is 1.05 times or more than the conversion efficiency of comparison object 1, as B when it is 1.00 times or more but less than 1.05 times the conversion efficiency of comparison object 1, and as C when it is less than 1.00 times the conversion efficiency of comparison object 1.
[0084] (Comparative Example A1) On the glass substrate 1, ITO (In:Sn=80:20, thickness 150 [nm]) and ATO (Sn:Sb=98:2, thickness 100 [nm]) are deposited on the top surface of the glass substrate 1 as a p-electrode 2 on the back side. A 6 [μm] thick Cu layer is deposited on the ATO as a p-type light absorbing layer 3 by sputtering in an oxygen and argon gas atmosphere. 2 After the p-type light absorbing layer 3 is formed, a thin Al layer is deposited by the ALD method. x1 O y A 10 nm thick Ga layer was formed as an n-type layer 4 directly on the p-type light absorbing layer 3 without forming a 2 O 3 A film is then formed. A 0.1 μm-thick AZO(ZnO:Al) film is then formed as the n-electrode 5 to obtain a solar cell. The solar cell is then evaluated in the same manner as in Example A1.
[0085] (Examples A2 to A13, Comparative Examples A2 to A7) Solar cells 100 of Examples A2 to A13 and Comparative Examples A2 to A7 were produced by changing the conditions for forming compound 6 of the first metal. The conditions for compound 6 of the first metal in the solar cell of Example A are shown in the table of Fig. 13. Evaluation results of the solar cell of Example A are shown in the table of Fig. 14. (Comparative example A8) On the glass substrate 1, ITO (In:Sn=80:20, thickness 150 [nm]) and ATO (Sn:Sb=98:2, thickness 100 [nm]) are deposited on the top surface of the glass substrate 1 as a p-electrode 2 on the back side. A 6 [μm] thick Cu layer is deposited on the ATO as a p-type light absorbing layer 3 by sputtering in an oxygen and argon gas atmosphere. 2 After the p-type light absorbing layer 3 is formed, a thin Al layer is deposited by the ALD method. x1 O y A 10 nm thick Ga layer was formed as an n-type layer 4 directly on the p-type light absorbing layer 3 without forming a 1.8 Al 0.2 O 3 A film is then formed. A 0.1 μm-thick AZO(ZnO:Al) film is then formed as the n-electrode 5 to obtain a solar cell. The solar cell is then evaluated in the same manner as in Example A1.
[0086] By forming an extremely thin first metal compound 6 between the p-type light absorbing layer 3 and the n-type layer 4 with a coverage of less than 100%, it is possible to suppress the extraction of oxygen from the p-type light absorbing layer 3 by the n-type layer 4, and the defects originating from metal Cu generated on the surface of the p-type light absorbing layer 3 due to the oxygen extraction are reduced. Therefore, Voc is improved. However, when the coverage exceeds 100%, FF and Jsc decrease due to the insulating property of the first metal compound 6. Furthermore, when the thickness of the first metal compound 6 becomes thick, not only FF and Jsc but also Voc decreases, so the conversion efficiency is significantly deteriorated. Since the first metal compound 6 is wide-gap and extremely thin, the transmittance does not change.
[0087] Example B Example B1 On the glass substrate 1, ITO (In:Sn=80:20, thickness 150 [nm]) and ATO (Sn:Sb=98:2, thickness 100 [nm]) are deposited on the top surface of the glass substrate 1 as a p-electrode 2 on the back side. A 6 [μm] thick Cu layer is deposited on the ATO as a p-type light absorbing layer 3 by sputtering in an oxygen and argon gas atmosphere. 2 After the p-type light absorbing layer 3 is formed, a thin Al layer is deposited by the ALD method. x1 O y A 10 nm thick Ga layer was formed as an n-type layer 4 directly on the p-type light absorbing layer 3 without forming a 2 O 3 A film is formed. 2 O 3 A 14 nm thick ZnSnO (Zn:Sn=80:20) film is then formed on the n-electrode 5. A 0.1 μm thick AZO (ZnO:Al) film is then formed as the n-electrode 5 to obtain the solar cell 100. The solar cell is then evaluated in the same manner as in Example A1.
[0088] (Comparative Example B1) On the glass substrate 1, ITO (In:Sn=80:20, thickness 150 [nm]) and ATO (Sn:Sb=98:2, thickness 100 [nm]) are deposited on the top surface of the glass substrate 1 as a p-electrode 2 on the back side. A 6 [μm] thick Cu layer is deposited on the ATO as a p-type light absorbing layer 3 by sputtering in an oxygen and argon gas atmosphere. 2 After the p-type light absorbing layer 3 is formed, a thin Al layer is deposited by the ALD method. x1 O y A 10 nm thick Ga layer was formed as an n-type layer 4 directly on the p-type light absorbing layer 3 without forming a 2 O 3 A film is formed. 2 O 3 A ZnSnO (Zn:Sn=80:20) film with a thickness of 14 nm is then formed on the n-electrode 5. A 0.1 μm thick AZO (ZnO:Al) film is then formed as the n-electrode 5 to obtain a solar cell. The solar cell is then evaluated in the same manner as in Example A1.
[0089] (Examples B2 to B13, Comparative Examples B2 to B7) Solar cells of Examples B2 to B13 and Comparative Examples B2 to B7 were produced by changing the conditions for forming compound 6 of the first metal. The conditions for compound 6 of the first metal in the solar cell of Example B are shown in the table of Fig. 15. Evaluation results of the solar cell of Example A are shown in the table of Fig. 16.
[0090] (Comparative example B8) On the glass substrate 1, ITO (In:Sn=80:20, thickness 150 [nm]) and ATO (Sn:Sb=98:2, thickness 100 [nm]) are deposited on the top surface of the glass substrate 1 as a p-electrode 2 on the back side. A 6 [μm] thick Cu layer is deposited on the ATO as a p-type light absorbing layer 3 by sputtering in an oxygen and argon gas atmosphere. 2 After the p-type light absorbing layer 3 is formed, a thin Al layer is deposited by the ALD method. x1 O y A 10 nm thick Ga layer was formed as an n-type layer 4 directly on the p-type light absorbing layer 3 without forming a 1.8 Al 0.2 O 3 A film is formed. 1.8 Al 0.2 O 3 A ZnSnO (Zn:Sn=80:20) film having a thickness of 14 nm is then formed on the n-electrode 5. A 0.1 μm AZO (ZnO:Al) film is then formed as the n-electrode 5 to obtain a solar cell. The solar cell is then evaluated in the same manner as in Example A1.
[0091] In comparison with Example A, in Example B, the second n-layer having a smaller band gap than the first n-layer is formed, so that carrier recombination between the n-type layer 4 and the n-electrode 5 can be suppressed, and FF is improved. By forming an extremely thin first metal compound 6 with a coverage rate of less than 100% between the p-type light absorbing layer 3 and the n-type layer 4, the extraction of oxygen from the p-type light absorbing layer 3 by the n-type layer 4 can be suppressed, and defects derived from metal Cu generated on the surface of the p-type light absorbing layer 3 due to oxygen extraction are reduced. Therefore, Voc is improved. However, as shown in the comparative example, when the coverage rate becomes 100%, FF and Jsc decrease due to the insulating property of the first metal compound 6. Furthermore, when the thickness of the first metal compound 6 becomes thick, not only FF and Jsc but also Voc decreases, so that the conversion efficiency is significantly deteriorated. Since the first metal compound 6 is wide-gap and extremely thin, the transmittance does not change.
[0092] The technical solutions of the embodiments are described below. Technical proposal 1 A p-electrode; An n-electrode; a p-type light absorbing layer mainly made of a cuprous oxide compound provided on the p-electrode; an n-type layer provided between the p-type light absorbing layer and the n-electrode; a compound of a first metal between the p-type light absorbing layer and the n-type layer; A coverage rate of the compound of the first metal covering the p-type absorber layer is 10% or more and less than 100%; The first metal is one or more elements selected from the group consisting of Al, Hf, Zr, and B, The cuprous oxide compound is in direct contact with the compound of the first metal and the n-type layer. Technical proposal 2 The compound of the first metal is Al x1 Hf x2 Zr x3 B x4 O y A compound represented by the formula: x1, x2, x3, and x4 satisfy 0.8≦x1+x2+x3+x4≦1.2, The solar cell according to Technical Proposal 1, wherein x1, x2, x3, x4 and y satisfy 0.3≦(x1+x2+x3+x4) / y≦0.8. Technical proposal 3 The compound of the first metal is Al x1 O y A compound represented by the formula: The solar cell according to Technical Proposal 1, wherein x1 and y satisfy 0.5≦x1 / y≦0.8. Technical proposal 4 The compound of the first metal is Hf x2 O y A compound represented by the formula: The solar cell according to Technical Proposal 1, wherein x2 and y satisfy 0.3≦x2 / y≦0.7. Technical proposal 5 The compound of the first metal is Zr x3 O y A compound represented by the formula: The solar cell according to Technical Proposal 1, wherein x3 and y satisfy 0.3≦x3 / y≦0.7. Technical plan 6 The compound of the first metal is B x4 O y A compound represented by the formula: The solar cell according to Technical Proposal 1, wherein x4 and y satisfy 0.5≦x4 / y≦0.8. Technical proposal 7 The solar cell according to any one of Technical Schemes 1 to 6, wherein the cuprous oxide compound has a cuprite structure. Technical proposal 8 The solar cell according to any one of Technical Schemes 1 to 7, wherein the coverage is 50% or more and less than 100%. Technical proposal 9 The solar cell according to any one of Technical Schemes 1 to 8, wherein the coverage is 60% or more and less than 100%. Technical proposal 10 A solar cell according to any one of Technical Schemes 1 to 9, wherein the average height of the compounds of the first metal is 0.2 nm or more and 1 nm or less. Technical proposal 11 A solar cell described in any one of Technical Solutions 1 to 10, wherein the maximum height of the compound of the first metal is 0.2 nm or more and 1 nm or less. Technical proposal 12 12. A solar cell according to any one of Technical Solutions 1 to 11, wherein a side surface of the compound of the first metal is in direct contact with the n-type layer. Technical proposal 13 A solar cell according to any one of Technical Solutions 1 to 12, wherein a surface of the compound of the first metal other than a surface facing the p-type light absorbing layer is in direct contact with the n-type layer. Technical proposal 14 A multi-junction solar cell using a solar cell according to any one of Technical Solutions 1 to 13. Technical proposal 15 A solar cell module using a solar cell according to any one of technical proposals 1 to 13. Technical proposal 16 A solar power generation system that generates electricity using the solar cell module described in Technical Proposal 15. In the present specification, some elements are shown only by their element symbols. [Explanation of symbols]
[0093] 1: Circuit board 2 :p electrode 3: p-type light absorbing layer 4:N-type layer 5 :n electrode 6: Compounds of first metals 100: Solar cell 200: Multijunction solar cell 201:Second solar cell 300: Solar cell module 301: First solar cell module 302: Second solar cell module 303: Submodule 304: Wiring 305: Busbar 400: Solar power generation system 401: Solar cell module 402: Converter 403: Battery 404: Load 500: Vehicle 501: Body 502: Solar cell module 503: Power conversion device 504: Battery 505: Motor 600: Flying object 601: Aircraft frame 602: Motor 603: Rotor 604: Control unit
Claims
1. A p-electrode; An n-electrode; a p-type light absorbing layer mainly made of a cuprous oxide compound provided on the p-electrode; an n-type layer provided between the p-type light absorbing layer and the n-electrode; a compound of a first metal between the p-type light absorbing layer and the n-type layer; a coverage of the p-type light absorbing layer by the compound of the first metal is equal to or greater than 10% and less than 100%; The first metal is one or more elements selected from the group consisting of Al, Hf, Zr, and B, The cuprous oxide compound is in direct contact with the compound of the first metal and the n-type layer.
2. The compound of the first metal is Al x1 Hf x2 Zr x3 B x4 O y A compound represented by the formula: x1, x2, x3, and x4 satisfy 0.8≦x1+x2+x3+x4≦1.2, 2. The solar cell according to claim 1, wherein x1, x2, x3, x4 and y satisfy 0.3≦(x1+x2+x3+x4) / y≦0.
8.
3. The compound of the first metal is Al x1 O y A compound represented by the formula: The solar cell according to claim 1 , wherein x1 and y satisfy 0.5≦x1 / y≦0.
8.
4. The compound of the first metal is Hf x2 O y A compound represented by the formula: The solar cell according to claim 1 , wherein x2 and y satisfy 0.3≦x2 / y≦0.
7.
5. The compound of the first metal is Zr x3 O y A compound represented by the formula: The solar cell according to claim 1 , wherein x3 and y satisfy 0.3≦x3 / y≦0.
7.
6. The compound of the first metal is B x4 O y A compound represented by the formula: The solar cell according to claim 1 , wherein x4 and y satisfy 0.5≦x4 / y≦0.
8.
7. The solar cell according to claim 1 , wherein the cuprous oxide compound has a cuprite structure.
8. The solar cell according to claim 1 , wherein the coverage is equal to or greater than 50% and less than 100%.
9. The solar cell according to claim 1 , wherein the coverage is equal to or greater than 60% and less than 100%.
10. The solar cell according to claim 1 , wherein an average height of the compound of the first metal is 0.2 nm or more and 1 nm or less.
11. The solar cell according to claim 1 , wherein the maximum height of the compound of the first metal is not less than 0.2 nm and not more than 1 nm.
12. The solar cell according to claim 1 , wherein a side surface of the compound of the first metal is in direct contact with the n-type layer.
13. The solar cell according to claim 1 , wherein a surface of the compound of the first metal other than a surface facing the p-type light absorbing layer is in direct contact with the n-type layer.
14. A multi-junction solar cell using the solar cell according to any one of claims 1 to 13.
15. A solar cell module using the solar cell according to any one of claims 1 to 13.
16. A solar power generation system that generates power using the solar cell module according to claim 15.
Citation Information
Patent Citations
Method of manufacturing photoelectric conversion element, method of manufacturing p-type semiconductor layer, and p-type semiconductor layer
JP2015162650A
Solar cell, multi-junction solar cell, solar cell module and photovoltaic power generation system
JP2021009957A
Solar cell, multi-junction solar cell, solar cell module, and solar power generation system
WO2020059053A1
Solar cell, multi-junction solar cell, solar cell module, and solar power generation system
WO2022074852A1
Solar cell, multi-junction solar cell, solar cell module, and solar power generation system
WO2023281760A1